Cross-technology legitimacy feedback: The politics of policy-led innovation for complementarity in concentrating solar power - Thonig, Richard; Lilliestam, Johan (Environmental Innovation and Societal Transitions, 2024)
Solar photovoltaic and wind power generation is expanding fast globally, fuelled by technological progress and rapid cost reductions. Other renewable power technologies fare much worse: deployment stagnates despite substantial technological progress. Here, we explore why these technologies fall off political agendas although they are improving, proposing that negative cross-technology feedback from more dynamic, faster deployed technologies reduce the legitimacy of laggard technologies. This generates political pressure to cancel or adapt support schemes, which in turn may push the laggard technology to change and become more complementary to the dynamic technologies. We illustrate our propositions with a case study of concentrating solar power (CSP) policy and deployment in three countries. We show how negative legitimacy feedback from the dynamic diffusion of photovoltaics and wind power in the 2010s led to both policy termination and technological adaptation towards complementarity, changing CSP from a generation to a storage and balancing technology.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Case study; Concentrating solar power; Diffusion of innovations; Lock-in; Niche markets; Transition mechanisms